MOLECULAR CHARACTERIZATION OF MULTIDRUG RESISTANT ESCHERICHIA COLI ISOLATED FROM URINARY TRACT INFECTIONS - Kuppuswamy, Amudha; Das, Nisha; Bhattacharyya, Epsita; Arjunan, Selvam; Rajan, Raja (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â KEY WORDS: E.coli, RAPD, PCR, Antibiotic resistance Â Abstract Objective: Molecular Characterization of Multidrug Resistant Escherichia coli Isolated from Urinary Tract Infections by RAPD analysis. Random Amplification of Polymorphic DNA (RAPD) is a method of DNA fingerprinting. It is called fingerprinting because the nucleotide sequence in the DNA of each individual organism varies even within the same species and hence generates a unique pattern upon amplification using primers that bind randomly in the genome. Methods: In this study Ten Escherichia coli samples isolated from the urine of several patients showing symptoms of urinary tract infection were collected from a Diagnostic Centre in Bangalore. The genus and species were confirmed by biochemical characterization according to Bergey's Manual for Characterization of Bacteria followed by PCR confirmation and constructing dendrogram based on primers used. The confirmed specimens were subjected to antibiotic sensitivity test using Kirby-Bauer Disk Diffusion Susceptibility Test protocol. The sensitivity of E. coli to a range of antibiotics including Nalidixic acid, Gentamycin, Trimethoprim and Sulfamethoxazole used in treatment of urinary tract infections was checked. Six multidrug resistant varieties of E. coli were identified. The genomic DNA of these bacterial samples was isolated using phenol chloroform extraction method. The DNA was estimated qualitatively using agarose gel electrophoresis and quantitatively using Nano-drop spectrophotometer. Using four decamer oligo-nucleotides as single primers in Polymerase Chain Reaction (PCR), DNA fingerprinting, dendrogram analysis and genetic similarity matrix were estimated, revealing variations between selected six strains of E. coli. Result: Amongst primers used, D-20 has shown clear distinctive band pattern and shows that samples 1 and 3 are closely related to each other and distantly related to 4 and 2. Samples 5 and 6 are closely related to each other but very distantly related to other samples phylogenetically.